Interview With the Norwegian Writer Nils-Øivind Haagensen - DUINEA, Raluca-Daniela (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Nils-Øivind Haagensen (b. 1971) is a Norwegian journalist, poet, writer and the head of Flamme Publishing House. He was born in Ålesund and at present he lives in Oslo, Norway. He made his literary debut in 1998 with the volume of poems Hender og hukommelse (Hands and Memories). In 2001 he published his first novel, Det radioaktige (The Radioactive). In 2004 he was awarded Sultprisen (Hunger Prize) for his literary work, and in 2013 he was nominated for Nordisk råds litteraturpris (Nordic Council Literature Prize) with the volume of poems God morgen og god natt (Good Morning and Good Night, 2012). He was also awarded the Stiftelsen Kjell Holms kulturpris (Stiftelsen Kjell Holm Culture Prize, 2017). In 2019 he published the novel Dette norske livet (This Norwegian Life), and in 2013 he published the novel Liten (Little). Sangria i parken (Sangria in the Park, 2021) is his most recent novel published by Oktober Publishing House. He also published a series of volumes of poems Det uregjerlige (Hard to Control, 2020), Stor (Big, 2018) and Spredning (Spreading, 2014).